Septin Remodeling During Mammalian Cytokinesis - Russo, Giulia; Krauss, Michael (Frontiers in Cell and Developmental Biology, 2021)
Cytokinesis mediates the final separation of a mother cell into two daughter cells. Septins are recruited to the cleavage furrow at an early stage. During cytokinetic progression the septin cytoskeleton is constantly rearranged, ultimately leading to a concentration of septins within the intercellular bridge (ICB), and to the formation of two rings adjacent to the midbody that aid ESCRT-dependent abscission. The molecular mechanisms underlying this behavior are poorly understood. Based on observations that septins can associate with actin, microtubules and associated motors, we review here established roles of septins in mammalian cytokinesis, and discuss, how septins may support cytokinetic progression by exerting their functions at particular sites. Finally, we discuss how this might be assisted by phosphoinositide-metabolizing enzymes.